2022
DOI: 10.3390/nu15010088
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of COVID-19 Pandemic and Lockdown on Pediatric Nutritional and Metabolic Diseases: A Narrative Review

Abstract: SARS-CoV-2 was the first pathogen implied in a worldwide health emergency in the last decade. Containment measures have been adopted by various countries to try to stop infection spread. Children and adolescents have been less clinically involved by COVID-19, but the pandemic and consequent containment measures have had an important influence on the developmental ages. The COVID-19 pandemic and the subsequent lockdown periods have influenced the nutrition and lifestyles of children and adolescents, playing an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 134 publications
1
10
0
1
Order By: Relevance
“…Moreover, food insecurity increased among the lowest-income families [20]. Altogether, all these elements are in agreement with the increased incidence of overweight, obesity and type 2 diabetes mellitus detected during the lockdown confinement [21].…”
Section: Discussionsupporting
confidence: 79%
“…Moreover, food insecurity increased among the lowest-income families [20]. Altogether, all these elements are in agreement with the increased incidence of overweight, obesity and type 2 diabetes mellitus detected during the lockdown confinement [21].…”
Section: Discussionsupporting
confidence: 79%
“…Additionally, this information can be collected across a hospital department or system to better understand the impacts of the specific isolation protocols in place. Such interventions might aid in detecting potentially deleterious impacts which might otherwise be masked after discharge from hospital while still in at-home social isolation [ 28 , 37 , 38 , 39 ]. While motor dexterity has been understudied in children following isolation, previous studies have found lower levels of motor dexterity in pediatric populations without chronic illness, which was coupled with cortical structural changes [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, the majority of available trials suggest that omega-3 fatty acids supplementation should be considered as a strategy for pediatric NAFLD due to their significant positive effects on hepatic fat content, insulin resistance, lipid levels and histological pathways ( Table 5 ). LCPUFAs supplementation should not be used as a single strategy but as a complement of nutritional and lifestyle interventions, which represent milestones in the cardiovascular disease prevention in developmental age [ 113 ]. Further studies are needed to evaluate long-term outcomes of LCPUFAs supplementation in pediatric patients with NAFLD and consequently on the associated cardiovascular diseases.…”
Section: Long-chain Polyunsaturated Fatty Acids (Lcpufas) In Cardiova...mentioning
confidence: 99%